EXPANDED DENGUE SYNDROME - Agustinus Vincent; Bramantono -; Usman Hadi; Muhammad Vitanata Arifijanto (Current Internal Medicine Research and Practice Surabaya Journal, 2022)
ABSTRACTDengue viral infection (DVI) is a debilitating arthropod-borne disease that has been rapidly spread in several regions of the world in recent years. The spectrum of disease varies from mild self-limiting illness to dengue fever (DF) to more severe and fulminating forms, i.e., dengue hemorrhagic fever (DHF), dengue shock syndrome (DSS),and expanded dengue syndrome (EDS). The pathogenesis of EDS is not clear amid lack of studies on animal models. In the absence of in vitro experiments, disease spectrum is difficult to be elucidated and mimicked for humans.Recent advances on research on atypical complications of EDS demonstrate the involvement of other major organs such as the kidney, lung, heart, and central nervous system. Histopathological findings demonstrate the presence of hemorrhage, edema, and inflammatory infiltrates in these organs.The spectrum of Dengue viral infection varies from mild self-limiting illness to dengue fever to more severe and fulminating forms, i.e., dengue hemorrhagic fever, dengue shock syndrome, and expanded dengue syndrome.  Apart from the classical presentation, dengue infection can result in a myriad of unusual clinical manifestations, which are grouped under the title expanded dengue syndrome. These findings urge more focused and comprehensive investigations to explore such relationships so that high-risk patients could be identified immediately during their presentation to the hospitals.Keywords: Expanded dengue syndrome, Pathogenesis, Organ-specific manifestation